2004
DOI: 10.1348/000712604773952458
|View full text |Cite
|
Sign up to set email alerts
|

A possible model for understanding the personality‐intelligence interface

Abstract: Despite the recent increase in the number of studies examining empirical links between personality and intelligence (see Hofstee, 2001; Zeidner & Matthews, 2000), a theoretical integration of ability and nonability traits remains largely unaddressed. This paper presents a possible conceptual framework for understanding the personality-intelligence interface. In doing so, it conceptualizes three different levels of intelligence, namely, intellectual ability (which comprises both Gf and Gc), IQ test performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
140
3
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(160 citation statements)
references
References 76 publications
15
140
3
2
Order By: Relevance
“…Personality traits and intellectual abilities have traditionally been seen as largely distinct domains. More recently, however, there is a renewed scientific interest concerning the relation between personality and intelligence as reflected by a growing number of research studies (Ackerman & Heggestad, 1997;Chamorro-Premuzic & Furnham, 2004). One particular personality trait that has been suggested to lie at the core of a possible personality-intelligence link is Openness to Experience, which reflects a person's willingness to explore, consider, and tolerate new experiences, ideas, and feelings.…”
Section: Openness To Experience Fluid Intelligence and Crystallizedmentioning
confidence: 99%
“…Personality traits and intellectual abilities have traditionally been seen as largely distinct domains. More recently, however, there is a renewed scientific interest concerning the relation between personality and intelligence as reflected by a growing number of research studies (Ackerman & Heggestad, 1997;Chamorro-Premuzic & Furnham, 2004). One particular personality trait that has been suggested to lie at the core of a possible personality-intelligence link is Openness to Experience, which reflects a person's willingness to explore, consider, and tolerate new experiences, ideas, and feelings.…”
Section: Openness To Experience Fluid Intelligence and Crystallizedmentioning
confidence: 99%
“…While the Big Five concept is empirical rather than a theory of personality (Srivastava, 2010), good reliability and consistency has been reported (de Raad & Schouwenburg, 1996;John et al, 2008). Chamorro-Premuzic & Furnham (2004) found that personality attributes measured using the big five construct accounted for up to 30% of the variance in academic performance at tertiary level education. There is a consensus across studies that conscientiousness is the best personality-based predictor of academic performance (O'Connor & Paunonen, 2007;Swanberg & Martinsen, 2010;Trapmann et al, 2007).…”
Section: Gqmentioning
confidence: 99%
“…There is a consensus across studies that conscientiousness is the best personality-based predictor of academic performance (O'Connor & Paunonen, 2007;Swanberg & Martinsen, 2010;Trapmann et al, 2007). Many researchers have cited conscientiousness as compensating for lower cognitive intelligence (see Chamorro-Premuzic & Furnham, 2004, and it is a consistent predictor of academic performance across assessment type (Allick & Realo, 1997;Kappe & van der Flier, 2010;Shute & Ventura, 2013).…”
Section: Gqmentioning
confidence: 99%
See 1 more Smart Citation
“…According to that model, individual differences can be conceptualized according to five basic dimensions: extraversion (E), neuroticism (N), openness to experience (O), agreeableness (A), and conscientiousness (C). Of the five, conscientiousness represents the dimension with higher consensus among researchers concerning its predictive value to academic performance (Bauer & Liang, 2003;Chamorro-Premuzic & Furnham, 2004, 2008Connor & Paunonen, 2007;Furnham, ChamorroPremuzic, & McDougall, 2002;Phillips, Abraham, & Bond, 2003). The remaining domains of personality are more controversial regarding their impact.…”
Section: Introductionmentioning
confidence: 99%